Typification of names published by Joseph Franz Freyn from eastern Turkey - Sutory, Karel (Phytotaxa, 2015)
In total 25 names were published by Joseph Franz Freyn based on collections by Anton Kronenburg originating from the surroundings of Lake Van (eastern Turkey). Only two of them are in current use, all the other ones are considered synonyms. For 19 names lectotypes are selected, three were already designated elsewhere, for two names possible holotypes are indicated.